Identification of Dynamic Capability and Personal Competency to Develop Innovative Performance - Basuki, Budi; Suhariadi, Fendy; Choirunnisa, Zuyyina (RSF Conference Series: Business, Management and Social Sciences, 2023)
The New Public Management Paradigm required the management of public sector organizations to transform by prioritizing the principles of competition, performance, and responsiveness in every bureaucratic behavior so that it could stimulate an increase in organizational performance results to become more effective and efficient. Seeing the demands for public administration reform, of course, the desires and demands of the community for the creation of public sector organizations that had high governance performance was increasing where this indicated the low performance of public sector management as an effort to achieve increased flexibility of public sector organizations in facing global challenges. This study aimed to identify dynamic management capability and personal competency to develop innovative performance. This study used a qualitative approach with a literature study method, a literature study consisting of detailed investigations, data collection of certain period of time, phenomena, and contexts to analyze the context and processes related to the theoretical issues being studied intrinsically from the literature used. This study concluded that there were cognitive dynamic capability and personal competence that must be possessed by public organizations to increase innovative performance in effective governance, namely thinking again, thinking ahead, and thinking across. These three factors encouraged transformational changes in governance that led to the formation of dynamic capabilities of Government/public sector organizations facing global challenges.